Mangrove management collaboration in the Marusu coastal region of Maros regency. Issue 1 (April 2020) - Yusran,; Sabar, A
Abstract: Coastal area is a gateway for various human development activities. In other words, the coastal region is the first time and received the most pressure compared to other regions. The aim of this study is to identify mangrove damage and its causes to formulate collaborative management that is more directed towards sustainable management while taking into aspects of the function and role of mangroves as a tool for natural coastal protection and security. The research conducted from April to November 2019 in the coastal area of Marusu, Maros Regency, South Sulawesi Province. Data collection is done through map analysis, survey and in-depth interviews. Mangrove ecosystem analysis, satellite imagery data and SWOT analysis are used to achieve the research objectives. The area of mangrove forests in 2009, 2014, 2016 and 2019 was 105.85 Ha, 101.07 Ha, 92.06 Ha and 100.06 Ha, respectively. Changes in land cover since 2009 towards the end of 2014, the conversion of mangrove forests into ponds and dry land agriculture from 2009 to 2014 covered 5.83 (5.51%) and 6.82 Ha (6.64%). Damage to mangrove forests contributes to abrasion, intrusion of sea water, and loss of habitat for animals such as birds, mammals, reptiles, insects, and various marine biota. SWOT analysis a sustainable management strategy in the form of SO. Zoning of mangrove ecosystems, into the core zone and cultivation zone. ST, Policies and regulations that are appropriate and binding. WO, Knowledge upgrading regarding the benefits of the existence of mangrove forests. WT, management of mangrove forests based on pentahelix partnerships.